La recherche des nombres caractéristiques pour le Systeme d’une classe d’equations differentielles à coefficients périodiques - Golokvosčius, P. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:П. Голоквосчюс. Отыскание характеристических чисел решений одного класса систем дифференциальных уравнений с периодическими коэффициантамиP. Golokvosčius. Vienos klasės diferencialinių lygčių su periodiniais koeficientais sistemų sprendinių charakteringų skaičių radimas